The Impact of Smartphone Used to Children's First Language Acquisition - Mauriza Hesti Nurkhofifah; Yudi Juniardi (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2023)
This research is entitled A Study of The Relevance Impact Mobile Phone Used in Children's First Language Acquisition. The goal is to explain what things happen to the event if it continues. As well as explaining the factors that cause the permissibility of playing cellphones excessively and the impacts that occur. In this case it is familiar to all of us. This is very common nowadays. There are two factors that can affect the process of child growth and development, namely external factors and internal factors. Therefore, researchers are very enthusiastic in discussing familiar events that are often seen, even experienced. Mobile phones do not always have a negative impact on everyday life. However, in this case or another, children are often allowed to hold or play their gadgets without any restrictions. Mobile phones also have a positive impact on early childhood. To find out, this research was conducted based on previous studies so that there are factual answers that the writer can take.